Assesment of Optimum Timber Extraction Methods Using Geographic Information System-Based Multi-Criteria Decision Support Method - Tas, Inanc; Akay, Abdullah Emin; Eker, Mehmet; Gumues, Selcuk; Demir, Murat; Acar, H. Hulusi; Ozdemir, Mehmet (Aves, 2024)
Timber extraction is a time-consuming and difficult stage of producing the wood-based forest products, involving economic and ecological sensitivity. In this study, it was aimed to determine the optimum extraction methods in terms of productivity and environmental effects by integrating the analytical hierarchy process (AHP) method with geographic information systems (GIS). The study was implemented in the coniferous stands located within the borders of Baharlar Forest Enterprise Chief (FEC) in Ayvac & imath;k Forest Enterprise Directorate (FED) in Bal & imath;kesir in T & uuml;rkiye. The main criteria in AHP were slope, skidding (transporting) distance, soil factor, stand age and yield. In the study, tractor skidding, tractor winching, chute system and skyline yarding methods were evaluated by considering environmental effects including residual tree damage and potential impacts on forest soil. In the solution phase, a total of eight suitability maps were produced for four extraction methods for productivity and environmental effects assessment. After the suitability maps were generated, digital data layers of working time were produced for each extraction method using equations about machine working times obtained from previous studies. As a result of the study, it was determined that skidding distance and slope were the criteria with the highest impact in almost all extraction methods for productivity and environmental aspects. In tractor skidding, it was found that soil factor and skidding distance have the highest impact in terms of environmental effects. When considering productivity, the results showed that the most commonly preferred extraction method was the tractor winching (43.30%), followed by the tractor skidding (25.34%). While the chute system was preferred in approximately 20.92% of the area, the least preferred method was the skyline yarding (10.44%). When evaluated in terms of environmental effects, it was determined that tractor skidding (34.02%) was widely preferred, followed by chute system (26.95%), tractor winching (20.96%) and skyline yarding (18.07%).
Keywords: GIS-based MCDM method; productive; stand damage; timber extraction; working time